Survey and assessment of the ocean renewable energy resources in the US Gulf of Mexico - Musial, Walter, author; Tegen, Suzanne, author; Driscoll, Rick, author; Spitsen, Paul, author; Roberts, Owen, author; Kilcher, Levi, author; Scott, George, author; Beiter, Philipp, author; Bureau of Ocean Energy Management, publisher (Colorado State University. Libraries, 2020)
The goal of this study is to survey potential offshore renewable energy sources in the GOM and quantify their feasibility relating to resource adequacy, technology maturity, and the potential for competitive cost. The study provides a review of available technologies and concepts for generating offshore renewable energy, including a high-level assessment of the current state of each technology and its potential for future advances. It provides a breakdown of resource capacity for each renewable energy technology as well as a recommendation that offshore wind be pursued for future study as it was found to be the most promising ocean renewable technology.
Prepared by and in collaboration with the National Renewable Energy Laboratory.
Keywords: Offshore wind power plants; Renewable energy sources -- Mexico, Gulf of